A method for preparing carbon fiber composite material

By adding TiO2 to the carbon fiber composite material and performing thermal decoupling, the shortcomings of existing materials in terms of mechanical properties and conductive properties are solved, and carbon fiber composite materials with high mechanical properties and conductive properties are achieved, which are suitable for high-performance applications such as fuel cell separators.

CN117209954BActive Publication Date: 2025-04-22HENAN GUANHE NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311335764.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-22
Estimated Expiration
2043-10-16

AI Technical Summary

Technical Problem

Existing carbon fiber composite materials have shortcomings in terms of mechanical properties and electrical conductivity, especially in the application of fuel cell separators, which are difficult to meet the requirements of electrical conductivity, mechanical strength and gas permeability.

Method used

TiO2-PAN composite fiber is prepared by adding TiO2 to polyacrylonitrile and thermally decoated in a tube furnace to gradually increase the carbon content and reduce the silicon content. Therefore, the modified carbon fiber material has good mechanical properties and surfactivity and can be evenly dispersed in the organic resin.

Benefits of technology

The modified carbon fiber composite material significantly improves tensile strength and bending strength, and reduces the preparation cost. It is suitable for high-performance applications such as fuel cell separators.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004495726020000081
    Figure BDA0004495726020000081
Patent Text Reader

Abstract

The present invention provides a method for preparing a carbon fiber composite material, the method comprising: 2 PAN composite fiber is placed in a tube furnace, and silane and organic hydrocarbon are introduced. Silane and organic hydrocarbon are 2 The surface of the PAN composite fiber is pyrolyzed and coated, wherein the carbon content gradually increases and the silicon content gradually decreases from the center to the periphery of the fiber. The modified carbon fiber material has good mechanical properties and surface activity and can be evenly dispersed in the organic resin. The modified carbon fiber material is used as a filler or frame material to improve the mechanical properties and electrical conductivity of the material. The composite material prepared by the present invention has good tensile strength and flexural strength, low preparation cost, and broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a carbon fiber composite material. Background Art

[0002] The separator for fuel cells is used as a supporting member of the unit cell and a channel for the reaction gas and the coolant, and the separator should have excellent conductivity, high mechanical strength, and low gas permeability. Graphite is generally used as a material that satisfies these characteristics. Pure graphite has great conductivity and corrosion resistance, but pure graphite has many pores and it is difficult to form channels therein.

[0003] Carbon fiber can also be used as a separator raw material, and carbon fiber composites are prepared from polyacrylonitrile (PAN) precursors. Carbon fiber composites prepared from polyacrylonitrile as precursors are brittle, easy to break and have poor mechanical properties.

[0004] The method to increase the mechanical properties of carbon fiber and reduce thermal conductivity is generally to coat the surface of carbon fiber with amorphous carbon material or silicon material. However, it is difficult for PAN material to adhere to silicon material, and it is difficult to improve the mechanical properties. The inventors found that when TiO2 is added to polyacrylonitrile, the decomposed silicon and amorphous carbon produce an anchoring effect on the surface of PAN fiber due to the addition of TiO2, which can improve the adhesion of silicon and carbon to the fiber surface. The amorphous carbon generated by acetylene on the surface can improve the dispersion performance between the material and phenolic resin, thereby improving the overall mechanical properties of the material, and then proposed the following invention. Summary of the invention

[0005] The present invention provides a method for preparing a carbon fiber composite material, the method comprising: placing a TiO2-PAN composite fiber in a tubular furnace, introducing silane and organic hydrocarbon, pyrolyzing and coating the surface of the TiO2-PAN composite fiber with the silane and organic hydrocarbon, wherein the carbon content gradually increases and the silicon content gradually decreases from the center to the periphery of the fiber, and the modified carbon fiber material has good mechanical properties and surface activity, and can be evenly dispersed in an organic resin, and the modified carbon fiber material is used as a filler or frame material therein to improve the mechanical properties and electrical conductivity of the material. The composite material prepared by the present invention has good tensile strength and flexural strength, low preparation cost, and broad application prospects.

[0006] A method for preparing a carbon fiber composite material, characterized in that the specific preparation steps include:

[0007] 1) uniformly dispersing polyacrylonitrile in N,N-dimethylformamide to form an electrospinning precursor solution, adding nano-titanium dioxide particles, and stirring until uniform to obtain a spinning solution, wherein the mass percentage of the nano-titanium dioxide particles in the polyacrylonitrile is 6-8%;

[0008] 2) spinning the spinning solution into fibers by electrospinning to prepare TiO2-PAN composite fibers;

[0009] 3) placing the TiO2-PAN composite fiber in a tubular heating furnace, introducing a mixed gas of acetylene and monosilane, heating to 350-400° C. for 3-4 hours, and uniformly reducing the amount of monosilane gas introduced during the heating process. After the amount of monosilane gas introduced is reduced to 0, continuing to introduce acetylene gas for heating for 0.5-1 hour, stopping the introduction of acetylene gas, introducing inert gas, heating the tubular furnace to 1000-1200° C., carbonizing for 4-6 hours, and cooling to obtain a carbon composite fiber with silicon and silicon-carbon composites coated on the surface;

[0010] 4) Mixing the composite fiber obtained in step 3 with a phenolic resin solution, and hot pressing to obtain the carbon fiber composite material.

[0011] Furthermore, in step 1), the mass ratio of polyacrylonitrile to N,N-dimethylformamide is 1:10-20.

[0012] Furthermore, in step 2), the spinning voltage is 20-25 kV, the flow rate is 0.5-1 mL / h, and the distance between the syringe needle and the collector is 15-20 cm.

[0013] Furthermore, in step 3), the initial gas flow rate is 50-100 ml / s, and the volume ratio of acetylene to monosilane gas in the initial gas is 1:3-5.

[0014] Furthermore, step 4) is as follows: adding phenolic resin to ethanol to obtain a phenolic resin solution, adding the composite fiber to the phenolic resin solution, dispersing evenly, adding a curing agent, hot pressing and curing in a mold, cooling, and demolding to obtain a carbon fiber composite material.

[0015] Furthermore, the mass ratio of phenolic resin to ethanol is 1:1.5-2, the mass ratio of the composite fiber to the phenolic resin solution is 1:0.8-1.2; the hot pressing temperature is 160-200°C, and the pressure is 3-5MPa.

[0016] Furthermore, the carbon fiber composite material is prepared by the method described.

[0017] Beneficial technical effects of the present invention

[0018] 1) After adding TiO2 to polyacrylonitrile, the decomposed silicon and amorphous carbon produce an anchoring effect on the surface of PAN fibers due to the addition of TiO2, which can improve the adhesion of silicon and carbon on the fiber surface and improve the mechanical properties of carbon fibers;

[0019] 2) Adjusting the ratio of silane to hydrocarbon to avoid the production of crystallized SiC during the carbonization process can improve the mechanical strength of the fiber.

[0020] 3) From the center to the periphery of the fiber, the carbon content gradually increases and the silicon content gradually decreases. The modified carbon fiber material has good mechanical properties and surface activity, which improves the mechanical properties of the product. DETAILED DESCRIPTION

[0021] The present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples within the scope not exceeding the gist of the present invention.

[0022] Example 1

[0023] 1) uniformly dispersing polyacrylonitrile in N,N-dimethylformamide, the mass ratio of polyacrylonitrile to N,N-dimethylformamide being 1:15, to form an electrospinning precursor solution, adding nano-titanium dioxide particles, and stirring until uniform to obtain a spinning solution, wherein the mass percentage of the nano-titanium dioxide particles in the polyacrylonitrile is 7%;

[0024] 2) spinning the spinning solution into fibers by electrospinning to prepare TiO2-PAN composite fibers, the spinning voltage was 25 kV, the flow rate was 1 mL / h, and the distance between the syringe needle and the collector was 20 cm;

[0025] 3) The TiO2-PAN composite fiber is placed in a tubular heating furnace, and a mixed gas of acetylene and monosilane is introduced. The initial gas flow rate is 100 ml / s, and the volume ratio of acetylene and monosilane gas in the initial gas is 1:4. The fiber is heated to 375°C. During the entire heating process, the amount of monosilane gas introduced is uniformly reduced. After heating for 4 hours, the amount of monosilane gas introduced is reduced to 0, and acetylene gas is continued to be introduced and heated at 375°C for 1 hour. The introduction of acetylene gas is stopped, and nitrogen is introduced. The tubular furnace is heated to 1100°C, carbonized for 6 hours, and cooled to obtain a carbon composite fiber with silicon and silicon-carbon composites coated on the surface;

[0026] 4) adding phenolic resin to ethanol, the mass ratio of phenolic resin to ethanol is 1:1.5, mixing evenly to obtain a phenolic resin solution, mixing the composite fiber and the phenolic resin solution evenly, the mass ratio of the composite fiber to the phenolic resin solution is 1:1, adding curing agent acetic acid, hot pressing and curing in a mold, the hot pressing temperature is 180°C, the pressure is 3MPa, cooling, demolding, and obtaining a carbon fiber composite material with a density of 1.3±0.01g / cm 3 .

[0027] Example 2

[0028] 1) uniformly dispersing polyacrylonitrile in N,N-dimethylformamide, the mass ratio of polyacrylonitrile to N,N-dimethylformamide being 1:10, to form an electrospinning precursor solution, adding nano-titanium dioxide particles, and stirring until uniform to obtain a spinning solution, wherein the mass percentage of the nano-titanium dioxide particles in the polyacrylonitrile is 6%;

[0029] 2) spinning the spinning solution into fibers by electrospinning to prepare TiO2-PAN composite fibers, the spinning voltage was 25 kV, the flow rate was 1 mL / h, and the distance between the syringe needle and the collector was 20 cm;

[0030] 3) The TiO2-PAN composite fiber is placed in a tubular heating furnace, and a mixed gas of acetylene and monosilane is introduced. The initial gas flow rate is 100 ml / s, and the volume ratio of acetylene and monosilane gas in the initial gas is 1:3. The fiber is heated to 350°C for 3 hours. During the heating process, the amount of monosilane gas introduced is uniformly reduced. After the amount of monosilane gas introduced is reduced to 0, acetylene gas is continued to be introduced for heating for 0.5 hours. The introduction of acetylene gas is stopped, and nitrogen is introduced. The tubular furnace is heated to 1000°C, carbonized for 4 hours, and cooled to obtain a carbon composite fiber with silicon and silicon-carbon composites coated on the surface;

[0031] 4) adding phenolic resin to ethanol, the mass ratio of phenolic resin to ethanol is 1:1.5, mixing evenly to obtain a phenolic resin solution, mixing the composite fiber and the phenolic resin solution evenly, the mass ratio of the composite fiber to the phenolic resin solution is 1:1, adding curing agent acetic acid, hot pressing and curing in a mold, the hot pressing temperature is 180°C, the pressure is 3MPa, cooling, demolding, and obtaining a carbon fiber composite material with a density of 1.3±0.01g / cm 3 .

[0032] Example 3

[0033] 1) uniformly dispersing polyacrylonitrile in N,N-dimethylformamide, the mass ratio of polyacrylonitrile to N,N-dimethylformamide being 1:20, to form an electrospinning precursor solution, adding nano-titanium dioxide particles, and stirring until uniform to obtain a spinning solution, wherein the mass percentage of the nano-titanium dioxide particles in the polyacrylonitrile is 8%;

[0034] 2) spinning the spinning solution into fibers by electrospinning to prepare TiO2-PAN composite fibers, the spinning voltage was 25 kV, the flow rate was 1 mL / h, and the distance between the syringe needle and the collector was 20 cm;

[0035] 3) The TiO2-PAN composite fiber is placed in a tubular heating furnace, and a mixed gas of acetylene and monosilane is introduced. The initial gas flow rate is 100 ml / s, and the volume ratio of acetylene and monosilane gas in the initial gas is 1:5. The fiber is heated to 400°C for 4 hours. During the heating process, the amount of monosilane gas introduced is uniformly reduced. After the amount of monosilane gas introduced is reduced to 0, acetylene gas is continued to be introduced for heating for 1 hour. The introduction of acetylene gas is stopped, and nitrogen is introduced. The tubular furnace is heated to 1200°C, carbonized for 4 hours, and cooled to obtain a carbon composite fiber with silicon and silicon-carbon composites coated on the surface;

[0036] 4) adding phenolic resin to ethanol, the mass ratio of phenolic resin to ethanol is 1:1.5, mixing evenly to obtain a phenolic resin solution, mixing the composite fiber and the phenolic resin solution evenly, the mass ratio of the composite fiber to the phenolic resin solution is 1:1, adding curing agent acetic acid, hot pressing and curing in a mold, the hot pressing temperature is 180°C, the pressure is 3MPa, cooling, demolding, and obtaining a carbon fiber composite material with a density of 1.3±0.01g / cm 3 .

[0037] Comparative Example 1

[0038] 1) uniformly dispersing polyacrylonitrile in N,N-dimethylformamide, with the mass ratio of polyacrylonitrile to N,N-dimethylformamide being 1:15, to form an electrospinning precursor solution;

[0039] 2) spinning the spinning solution into fibers by electrospinning to prepare PAN fibers, the spinning voltage was 25 kV, the flow rate was 1 mL / h, and the distance between the syringe needle and the collector was 20 cm;

[0040] 3) placing the PAN fiber in a tubular heating furnace, introducing nitrogen, heating the tubular furnace to 1100°C, carbonizing for 6 hours, and cooling to obtain carbon fiber;

[0041] 4) adding phenolic resin to ethanol, the mass ratio of phenolic resin to ethanol is 1:1.5, mixing evenly to obtain a phenolic resin solution, mixing the fiber and the phenolic resin solution evenly, the mass ratio of the fiber to the phenolic resin solution is 1:1, adding curing agent acetic acid, hot pressing and curing in a mold, the hot pressing temperature is 180°C, the pressure is 3MPa, cooling, demolding, and obtaining a carbon fiber composite material with a density of 1.3±0.01g / cm 3 .

[0042] Comparative Example 2

[0043] 1) uniformly dispersing polyacrylonitrile in N,N-dimethylformamide, the mass ratio of polyacrylonitrile to N,N-dimethylformamide being 1:15, to form an electrospinning precursor solution, adding nano-titanium dioxide particles, and stirring until uniform to obtain a spinning solution, wherein the mass percentage of the nano-titanium dioxide particles in the polyacrylonitrile is 7%;

[0044] 2) spinning the spinning solution into fibers by electrospinning to prepare TiO2-PAN composite fibers, the spinning voltage was 25 kV, the flow rate was 1 mL / h, and the distance between the syringe needle and the collector was 20 cm;

[0045] 3) placing the TiO2-PAN composite fiber in a tubular heating furnace, introducing nitrogen, heating the tubular furnace to 1100°C, carbonizing for 6 hours, and cooling to obtain carbon fiber;

[0046] 4) adding phenolic resin to ethanol, the mass ratio of phenolic resin to ethanol is 1:1.5, mixing evenly to obtain a phenolic resin solution, mixing the fiber and the phenolic resin solution evenly, the mass ratio of the fiber to the phenolic resin solution is 1:1, adding curing agent acetic acid, hot pressing and curing in a mold, the hot pressing temperature is 180°C, the pressure is 3MPa, cooling, demolding, and obtaining a carbon fiber composite material with a density of 1.3±0.01g / cm 3 .

[0047] Comparative Example 3

[0048] 1) uniformly dispersing polyacrylonitrile in N,N-dimethylformamide, with the mass ratio of polyacrylonitrile to N,N-dimethylformamide being 1:15, to form an electrospinning precursor solution;

[0049] 2) spinning the spinning solution into fibers by electrospinning to prepare PAN fibers, the spinning voltage was 25 kV, the flow rate was 1 mL / h, and the distance between the syringe needle and the collector was 20 cm;

[0050] 3) placing the PAN composite fiber in a tubular heating furnace, introducing a mixed gas of acetylene and monosilane, the initial gas flow rate of which is 100 ml / s, the volume ratio of acetylene to monosilane gas in the initial gas being 1:4, heating to 375°C, uniformly reducing the amount of monosilane gas introduced during the entire heating process, heating for 4 hours, the amount of monosilane gas introduced is reduced to 0, continuing to introduce acetylene gas and continuing to heat at 375°C for 1 hour, stopping the introduction of acetylene gas, introducing nitrogen, heating the tubular furnace to 1100°C, carbonizing for 6 hours, cooling, and obtaining a carbon composite fiber with silicon and silicon-carbon composites coated on the surface;

[0051] 4) adding phenolic resin to ethanol, the mass ratio of phenolic resin to ethanol is 1:1.5, mixing evenly to obtain a phenolic resin solution, mixing the composite fiber and the phenolic resin solution evenly, the mass ratio of the composite fiber to the phenolic resin solution is 1:1, adding curing agent acetic acid, hot pressing and curing in a mold, the hot pressing temperature is 180°C, the pressure is 3MPa, cooling, demolding, and obtaining a carbon fiber composite material with a density of 1.3±0.01g / cm 3 .

[0052] Comparative Example 4

[0053] 1) uniformly dispersing polyacrylonitrile in N,N-dimethylformamide, the mass ratio of polyacrylonitrile to N,N-dimethylformamide being 1:15, to form an electrospinning precursor solution, adding nano-titanium dioxide particles, and stirring until uniform to obtain a spinning solution, wherein the mass percentage of the nano-titanium dioxide particles in the polyacrylonitrile is 7%;

[0054] 2) spinning the spinning solution into fibers by electrospinning to prepare TiO2-PAN composite fibers, the spinning voltage was 25 kV, the flow rate was 1 mL / h, and the distance between the syringe needle and the collector was 20 cm;

[0055] 3) The TiO2-PAN composite fiber is placed in a tubular heating furnace, and a mixed gas of acetylene and monosilane is introduced. The initial gas flow rate is 100 ml / s, and the volume ratio of acetylene to monosilane gas is 1:2. The fiber is heated to 375°C. After heating for 4 hours, nitrogen is introduced, and the tubular furnace is heated to 1100°C. The fiber is carbonized for 6 hours and cooled to obtain a carbon composite fiber with silicon and silicon-carbon composites coated on the surface.

[0056] 4) adding phenolic resin to ethanol, the mass ratio of phenolic resin to ethanol is 1:1.5, mixing evenly to obtain a phenolic resin solution, mixing the composite fiber and the phenolic resin solution evenly, the mass ratio of the composite fiber to the phenolic resin solution is 1:1, adding curing agent acetic acid, hot pressing and curing in a mold, the hot pressing temperature is 180°C, the pressure is 3MPa, cooling, demolding, and obtaining a carbon fiber composite material with a density of 1.3±0.01g / cm 3 .

[0057] Comparative Example 5

[0058] 1) uniformly dispersing polyacrylonitrile in N,N-dimethylformamide, the mass ratio of polyacrylonitrile to N,N-dimethylformamide being 1:15, to form an electrospinning precursor solution, adding nano-titanium dioxide particles, and stirring until uniform to obtain a spinning solution, wherein the mass percentage of the nano-titanium dioxide particles in the polyacrylonitrile is 7%;

[0059] 2) spinning the spinning solution into fibers by electrospinning to prepare TiO2-PAN composite fibers, the spinning voltage was 25 kV, the flow rate was 1 mL / h, and the distance between the syringe needle and the collector was 20 cm;

[0060] 3) The TiO2-PAN composite fiber is placed in a tubular heating furnace, monosilane gas is introduced at an initial gas flow rate of 100 ml / s, and the fiber is heated to 375°C. After heating for 4 hours, the introduction of monosilane gas is stopped, and acetylene gas is introduced to continue heating at 375°C for 1 hour. The introduction of acetylene gas is stopped, and nitrogen is introduced. The tubular furnace is heated to 1100°C, carbonized for 6 hours, and cooled to obtain a carbon composite fiber with silicon and silicon-carbon composites coated on the surface;

[0061] 4) adding phenolic resin to ethanol, the mass ratio of phenolic resin to ethanol is 1:1.5, mixing evenly to obtain a phenolic resin solution, mixing the composite fiber and the phenolic resin solution evenly, the mass ratio of the composite fiber to the phenolic resin solution is 1:1, adding curing agent acetic acid, hot pressing and curing in a mold, the hot pressing temperature is 180°C, the pressure is 3MPa, cooling, demolding, and obtaining a carbon fiber composite material with a density of 1.3±0.01g / cm 3 .

[0062] Comparative Example 6

[0063] 1) uniformly dispersing polyacrylonitrile in N,N-dimethylformamide, the mass ratio of polyacrylonitrile to N,N-dimethylformamide being 1:15, to form an electrospinning precursor solution, adding nano-titanium dioxide particles, and stirring until uniform to obtain a spinning solution, wherein the mass percentage of the nano-titanium dioxide particles in the polyacrylonitrile is 7%;

[0064] 2) spinning the spinning solution into fibers by electrospinning to prepare TiO2-PAN composite fibers, the spinning voltage was 25 kV, the flow rate was 1 mL / h, and the distance between the syringe needle and the collector was 20 cm;

[0065] 3) The TiO2-PAN composite fiber is placed in a tubular heating furnace, and a mixed gas of acetylene and monosilane is introduced. The initial gas flow rate is 100 ml / s, and the volume ratio of acetylene and monosilane gas in the initial gas is 1:2. The fiber is heated to 375°C. After heating for 4 hours, acetylene gas is introduced and continued to be heated at 375°C for 1 hour. The introduction of acetylene gas is stopped, and nitrogen is introduced. The tubular furnace is heated to 1100°C, carbonized for 6 hours, and cooled to obtain a carbon composite fiber with silicon and silicon-carbon composites coated on the surface;

[0066] 4) adding phenolic resin to ethanol, the mass ratio of phenolic resin to ethanol is 1:1.5, mixing evenly to obtain a phenolic resin solution, mixing the composite fiber and the phenolic resin solution evenly, the mass ratio of the composite fiber to the phenolic resin solution is 1:1, adding curing agent acetic acid, hot pressing and curing in a mold, the hot pressing temperature is 180°C, the pressure is 3MPa, cooling, demolding, and obtaining a carbon fiber composite material with a density of 1.3±0.01g / cm 3 .

[0067] Comparative Example 7

[0068] 1) uniformly dispersing polyacrylonitrile in N,N-dimethylformamide, the mass ratio of polyacrylonitrile to N,N-dimethylformamide being 1:15, to form an electrospinning precursor solution, adding nano-titanium dioxide particles, and stirring until uniform to obtain a spinning solution, wherein the mass percentage of the nano-titanium dioxide particles in the polyacrylonitrile is 7%;

[0069] 2) spinning the spinning solution into fibers by electrospinning to prepare TiO2-PAN composite fibers, the spinning voltage was 25 kV, the flow rate was 1 mL / h, and the distance between the syringe needle and the collector was 20 cm;

[0070] 3) The TiO2-PAN composite fiber is placed in a tubular heating furnace, and a mixed gas of acetylene and monosilane is introduced. The initial gas flow rate is 100 ml / s, and the volume ratio of acetylene and monosilane in the initial gas is 1:4. The fiber is heated to 375°C. After heating for 4 hours, acetylene gas is continued to be introduced and heated at 375°C for 1 hour. The introduction of acetylene gas is stopped, and nitrogen is introduced. The tubular furnace is heated to 1100°C, carbonized for 6 hours, and cooled to obtain a carbon composite fiber with silicon and silicon-carbon composites coated on the surface;

[0071] 4) adding phenolic resin to ethanol, the mass ratio of phenolic resin to ethanol is 1:1.5, mixing evenly to obtain a phenolic resin solution, mixing the composite fiber and the phenolic resin solution evenly, the mass ratio of the composite fiber to the phenolic resin solution is 1:1, adding curing agent acetic acid, hot pressing and curing in a mold, the hot pressing temperature is 180°C, the pressure is 3MPa, cooling, demolding, and obtaining a carbon fiber composite material with a density of 1.3±0.01g / cm 3 .

[0072] Experimental results

[0073] The tensile performance test was carried out according to ISO527, the sample size was 150*10*4mm, and the tensile speed was 50mm / min;

[0074] The bending performance test was carried out according to ISO178, the sample size was 80*10*4mm, and the bending speed was 2mm / min

[0075] Table 1

[0076]

[0077] It can be seen from Comparative Examples 1-2 that the mechanical properties and conductivity of uncoated PAN carbon fibers are poor, and the addition of titanium dioxide itself does not have a positive effect on the mechanical properties and conductivity of PAN carbon fibers; it can be seen from Comparative Example 3 that titanium dioxide mainly affects the coating effect. When titanium dioxide is not doped, only the coating process of the present invention has limited effect on improving the mechanical properties of the material; it can be seen from Comparative Examples 4 and 6 that the carbon coating on the surface of the carbon fiber mainly improves the conductivity of the material; it can be seen from Comparative Documents 5 and 7 that the carbon-silicon content gradient layer has a more obvious effect on improving the conductivity and mechanical properties, and a simple silicon layer or a silicon carbide layer is not conducive to improving the conductivity and mechanical properties.

[0078] Although the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention.

Claims

1. A method for preparing a carbon fiber composite material, characterized in that: The specific preparation steps include: 1) uniformly dispersing polyacrylonitrile in N,N-dimethylformamide, the mass ratio of polyacrylonitrile to N,N-dimethylformamide being 1:10-20, to form an electrospinning precursor solution, adding nano-titanium dioxide particles, and stirring until uniform to obtain a spinning solution, wherein the mass percentage of the nano-titanium dioxide particles in the polyacrylonitrile is 6-8%; 2) spinning the spinning solution into fibers by electrospinning, the spinning voltage is 20-25 kV, the flow rate is 0.5-1 mL / h, and the distance between the syringe needle and the collector is 15-20 cm, thereby preparing TiO2-PAN composite fibers; 3) placing the TiO2-PAN composite fiber in a tubular heating furnace, introducing a mixed gas of acetylene and monosilane, the initial gas flow rate of which is 50-100 ml / s, the volume ratio of acetylene to monosilane gas in the initial gas being 1:3-5, heating to 350-400°C for 3-4 hours, uniformly reducing the amount of monosilane gas introduced during the heating process, and continuing to introduce acetylene gas for 0.5-1 hour after the amount of monosilane gas introduced is reduced to 0, stopping the introduction of acetylene gas, introducing inert gas, heating the tubular furnace to 1000-1200°C, carbonizing for 4-6 hours, cooling, and obtaining a carbon composite fiber with silicon and silicon-carbon composites coated on the surface; 4) Add phenolic resin to ethanol, the mass ratio of phenolic resin to ethanol is 1:1.5-2, to obtain a phenolic resin solution, then add the composite fiber obtained in step 3 to the phenolic resin solution, the mass ratio of the composite fiber to the phenolic resin solution is 1:0.8-1.2, disperse evenly, add a curing agent, hot press and cure in a mold, the hot pressing temperature is 160-200°C, the pressure is 3-5Mpa, cool, demold, and obtain a carbon fiber composite material.

2. A carbon fiber composite material, characterized in that: The carbon fiber composite material is prepared by the method according to claim 1.

Citation Information

Patent Citations

  • Composite reinforced material with interpenetrating network structure and preparation method of composite reinforced material

    CN109505037A

  • Basalt oil pipeline

    CN116877795A